2019
DOI: 10.1097/scs.0000000000004795
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants With a Platform-Switched Morse Taper Connection and an Osteo Growth Induction Surface

Abstract: Aim: The aim of this study was to analyze the clinical outcomes after using an innovative implant system characterized by a modern platform-switched Morse taper connection and an osteo growth induction titanium surface (a particular type of SLA surface). Peri-implant bone loss (PBL) and implant success rate were examined after a 1- to 3-year follow-up. Methods: The study was conducted as a cross-sectional analysis on all patients treated from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[ 37 ] By contrast, the low porosity of high‐density PTFE is known to prevent cell and bacteria adhesion and therefore is generally associated with a reduced risk of infection. [ 11 ] However, a clinical trial conducted by Ronda et al. [ 38 ] did not show any difference between ePTFE and high‐density PTFE membranes.…”
Section: Commercially Available Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] By contrast, the low porosity of high‐density PTFE is known to prevent cell and bacteria adhesion and therefore is generally associated with a reduced risk of infection. [ 11 ] However, a clinical trial conducted by Ronda et al. [ 38 ] did not show any difference between ePTFE and high‐density PTFE membranes.…”
Section: Commercially Available Membranesmentioning
confidence: 99%
“…[ 9 ] However, nonresorbable membranes suffer from various drawbacks, as their stiffness may cause soft tissue dehiscence, which can lead to the membrane exposure and subsequent infection. [ 11,12 ] Additionally, a second surgery is needed to remove nonresorbable membranes, resulting in patient discomfort and higher economic burden. [ 13,14 ] Synthetic and naturally derived resorbable membranes have been developed to avoid the need for a second surgical intervention and to reduce the risks of membrane exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques have been developed over the years to coat or chemically modify Ti implantable surfaces for dental applications in order to improve the implant response to oral microbiota. The objective of these interventions, in most cases, is achieved as a secondary effect for having enhanced the osseointegration process [11,12,13,14,15,16,17,18,19]. The risk of an early implant infection is indeed reduced by shortening the time for eukaryotic cells adhesion and osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the contribution of PS still arguable; resorption of crestal bone is to be affected by various factors. (23)(24)(25) The results of pocket depths in that study revealed that there were no statistically significant differences between the studied 2 groups during the follow-up periods except at loading. This indicates that probing depth is not influenced by platform switching.…”
Section: Discussionmentioning
confidence: 72%